2022
DOI: 10.1001/jama.2022.21820
|View full text |Cite
|
Sign up to set email alerts
|

Effect of a Community Health Worker–Delivered Personal Sound Amplification Device on Self-Perceived Communication Function in Older Adults With Hearing Loss

Abstract: ImportanceAge-related hearing loss that impairs daily communication is associated with adverse health outcomes, but use of hearing aids by older adults is low and disparities exist.ObjectiveTo test whether an affordable, accessible hearing care intervention, delivered by community health workers using over-the-counter hearing technology, could improve self-perceived communication function among older adults with hearing loss compared with a wait-list control.Design, Setting, and ParticipantsOpen-label randomiz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
43
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(43 citation statements)
references
References 37 publications
0
43
0
Order By: Relevance
“…While several personal sound amplification devices demonstrated similar speech understanding to traditional hearing aids, their outcome on health-related quality of life remains unknown . Further, a recent randomized clinical trial found that community health worker–delivered personal sound amplification devices improved patient-rated communication . We found that the maximum potential monetary value (or EVPI) of further research projects clarifying several of these uncertain parameters for OTC hearing aids is $25.6 billion, indicating that research investments into the effects of OTC hearing aid provisions are likely warranted.…”
Section: Discussionmentioning
confidence: 89%
“…While several personal sound amplification devices demonstrated similar speech understanding to traditional hearing aids, their outcome on health-related quality of life remains unknown . Further, a recent randomized clinical trial found that community health worker–delivered personal sound amplification devices improved patient-rated communication . We found that the maximum potential monetary value (or EVPI) of further research projects clarifying several of these uncertain parameters for OTC hearing aids is $25.6 billion, indicating that research investments into the effects of OTC hearing aid provisions are likely warranted.…”
Section: Discussionmentioning
confidence: 89%
“…A recent review [12] of Community-Based Hearing Rehabilitation (CBHR) reports on the value of this approach to improve access to hearing care. The majority of studies, however, are from high-income countries and focus on screening and assessment [13]. More research in LMICs where accessibility challenges are greatest is necessary across the hearing care journey to develop and support global action for improved access to care.…”
Section: Innovation In Delivery Of Hearing Carementioning
confidence: 99%
“…Programs involving paraprofessionals such as CHWs rather than medical personnel have been successful in supporting client health, including members of populations that are typically seen as "hard-to-reach" [36]. Notably, one program in which CHWs delivered hearing aids to elders living independently in the community found that self-reported communication skills of the experimental group improved significantly (p ≤ 0.05) compared to those of a control group [37]. CHWs could also educate individuals on methods for "falling safely" by controlling anxiety, avoiding panic, and protecting vulnerable parts of the body (e.g., as described by Zimmerman) [38].…”
Section: Public-and Community-based Health Approaches To Cmdmentioning
confidence: 99%